Financing State and Local Governments - Aronson, J. Richard; Hilley, John L.; Maxwell, James Ackley (Washington, D.C. : Brookings Institution, 1986)
This edition examines the incidence of the major state and local taxes, with emphasis to there ability to own up debt burden in there domain.
Third ed. by James A. Maxwell and J. Richard Aronson.
Includes index.
Bibliography: p. 255-258.
osc 15/06/17, ijb 14/03/2019
Loans
Keywords: Finance, Public; Local finance; Intergovernmental fiscal relations